The Effect of Oral Function Improvement on Dietary Habits in Older Adults Requiring Support Care - Kazuya Ikenishi; Akio Tada (Nursing Research and Practice)
Conclusions: Oral function training improved the oral function of older adults but could not change their dietary habits. Diet improvement may require dietary counseling together with oral exercise.